IN LIGHT OF THE CURRENT ECONOMIC STATUS: DO BOARD CHARACTERISTICS AND RISK MANAGEMENT COMMITTEES PROMOTE FIRM PERFORMANCE IN SAUDI ARABIA? - Alabdullah, Tariq Tawfeeq Yousif (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
The current study aimed to investigate the impact of corporate governance mechanisms on the profitability of listed companies within the Saudi Stock Exchange (SSE). The methodology involved data collection from the SSE for the fiscal year 2021, with a research sample comprising 60 corporations. The study's independent variables encompassed the size of the board of directors, frequency of board meetings, and the presence of risk management practices. The dependent variable was corporate performance, as indicated by the return on assets (ROA). To enhance the evaluation of the relationship between the independent variables and the dependent variable, the study also incorporated a control variable - the size of the corporation. The study's findings unveiled that a larger board size had a positive impact on the performance of Saudi corporations. Furthermore, both an increased frequency of board meetings and the implementation of risk management practices exhibited positive effects on corporate performance. This research contributes significantly by exploring the direct influence of board size, board meeting frequency, and risk management practices on the performance of SSE-listed companies. The study's novelty lies in its comprehensive examination of these specific corporate governance mechanisms and their correlation with return on assets.